TAR RNA binding properties and relative transactivation activities of human immunodeficiency virus type 1 and 2 Tat proteins. - Rhim, H (1993)
Using gel shift assays, we found that the human immunodeficiency virus type 1 (HIV-1) Tat protein (Tat-1) bound both HIV-1 and HIV-2 TAR RNAs with similar high affinities. In contrast, the HIV-2 Tat protein (Tat-2) bound only TAR-2 RNA with high affinity. We conclude that the weak in vivo activity of Tat-2 on the HIV-1 long terminal repeat that has been observed previously is likely the result of low affinity for TAR-1 RNA. Additionally, TAR-2 RNA was found to contain multiple specific binding sites for Tat proteins. GAL4-Tat fusion proteins were analyzed to compare the relative transactivation activities of Tat-1 and Tat-2 in the absence of requirements for binding to TAR RNAs. The GAL4-Tat-2 protein was found to transactivate synthetic promoters containing GAL4 binding sites at levels severalfold higher than did the GAL4-Tat-1 protein.